İcra ve iflâs hukukunda ihalenin feshi - Koçak, Nurgül (Fatih Sultan Mehmet Vakıf Üniversitesi, 2025)
Yargı mercilerinin vermiş olduğu kararlar ve öğretideki görüşler dikkate alınarak hazırlanan bu çalışmada, İcra ve İflâs Kanunu'nda düzenlenen ihalenin feshi kurumuna yönelik açıklamalar yer almaktadır. Söz konusu kurum tarihsel süreç içinde birçok değişikliğe uğramıştır. 7343 sayılı Kanunla ihalenin feshi kurumuna yönelik önemli değişiklikler yapılmıştır. Bu bağlamda ihalenin feshini talep edebilecek kişiler, hukuki yarar, ihalenin feshi talebinde bulunulurken yatırılması gereken harcın türü, gösterilmesi gereken teminat, icra mahkemesi tarafından verilen kararın niteliği gibi konuların incelenmesi ihtiyacı gerekmiştir.

In this study, which is prepared considering the decisions made by judicial authorities and the views in legal doctrine, explanations regarding the institution of cancellation of the auction as regulated in the Enforcement and Bankruptcy Law are provided. This institution has undergone many changes over time. Significant amendments were made to the institution of auction cancellation with Law No. 7343. In this context, it became necessary to examine issues such as who can request the cancellation of the auction, the legal interest, the type of fee that must be paid when requesting the cancellation, the collateral that needs to be provided, and the nature of the decision given by the enforcement court.
Termination of tender in execution and bankruptcy law
Keywords: Hukuk; Law